2022
DOI: 10.5781/jwj.2022.40.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Review on Vacuum Laser Beam Welding

Abstract: Vacuum laser beam welding (VLBW) exhibits better welding characteristics, e.g., deep penetration, less pore, and spatter generation, compared with the conventional laser welding technique under atmospheric pressure. Low ambient pressure affects the vaporization temperature of the base material and the interaction between laser and plasma plume, which affects the behaviors of laser-induced plasma plume, keyhole, and weld pool flow. This review introduces improvements in welding characteristics such as penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the rate of the anode reaction can be controlled via grain refinement, but it has minimal effect on the rate of the cathode reaction. 59,60 With the increases in WFR, the coarsening of the grains results in lower grain boundary density and anode reaction to accelerate, which deteriorates the corrosion resistance of LHW welded Inconel alloy. 61,62…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the rate of the anode reaction can be controlled via grain refinement, but it has minimal effect on the rate of the cathode reaction. 59,60 With the increases in WFR, the coarsening of the grains results in lower grain boundary density and anode reaction to accelerate, which deteriorates the corrosion resistance of LHW welded Inconel alloy. 61,62…”
Section: Resultsmentioning
confidence: 99%